A Critical Assessment of the Value of Top-Down and Bottom-Up Public Policy Implementation Theories, with Reference to the Case of Implementation of Passport Seva: An eGovernance Policy in India. (December 2021) - Balamurugan, K.
What are the challenges in public policy processes? Why do some critical public problems not carry to the agenda-setting of policy-making, or even if carried, they fail during implementation? One of the responses to these queries is that policy-making often happens in a complex, dynamic, sociopolitical environment where there are overarching structures above the policy makers and there are competing actors, ideas, groups, policy networks, institutions and policy subsystem that interact with unequal power and conflicting interests (Sanderson, 2009). It is thus realised that the systematic study of public policy is significant for bringing progressive change in society. Hence it is required to build new knowledge and to improve upon the working of public policy. This article will study the value of the top down and bottom up theories in the case of implementation of a new eGovernance policy on passport issuance in India. The findings are that due to resistance from different stakeholders, the project could be implemented only after certain bottom up changes to the policy along with change management strategies.